City and arts as a space for the reconstruction of history - Perdomo Vanegas, William Leonardo; López Pineda, Leidy Yohanna (Street Art & Urban Creativity, 2025)
This article presents the results of a research project aimed at creating a space for citizen participation, enabling reflection and recognition of the past in a region long celebrated for its cultural and artistic heritage. It explores how social and historical phenomena were interpreted through artistic creation in collaboration with the community of San Martín (Meta, Colombia). The discussion begins with an examination of art’s role in facilitating social interaction, followed by an overview of the activities conducted using a mixed methodology that combines action research and creative research. This is followed by an analysis of the artistic expressions produced by local artists. The article concludes with a consideration of the outcomes of the project, focusing on memory, history, and heritage as experienced through the creation of a collective artistic space.